2020
DOI: 10.1111/jne.12885
|View full text |Cite
|
Sign up to set email alerts
|

Anterior pituitary gland synthesises dopamine from l‐3,4‐dihydroxyphenylalanine (l‐dopa)

Abstract: Prolactin (PRL) is a hormone principally secreted by lactotrophs of the anterior pituitary gland. Although the synthesis and exocytosis of this hormone are mainly under the regulation of hypothalamic dopamine (DA), the possibility that the anterior pituitary synthesizes this catecholamine remains unclear. In this study, our aim was to determine if the anterior pituitary produces DA from the precursor L-Dopa. To this purpose, we studied the expression of aromatic L-amino acid decarboxylase (AADC) enzyme and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The genetic algorithm employed in SOM AI PRO identified that SOM3355 had VMAT2 inhibitory activity, which was confirmed in vitro, with an IC50 in the nanomolar range similar to TBZ. The increase in plasma prolactin levels observed after treatment with SOM3355 is consistent with that seen with other VMAT2 inhibitors, 39 and probably reflects a reduction in dopaminergic tone in the hypothalamus and/or pituitary gland 40,41 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The genetic algorithm employed in SOM AI PRO identified that SOM3355 had VMAT2 inhibitory activity, which was confirmed in vitro, with an IC50 in the nanomolar range similar to TBZ. The increase in plasma prolactin levels observed after treatment with SOM3355 is consistent with that seen with other VMAT2 inhibitors, 39 and probably reflects a reduction in dopaminergic tone in the hypothalamus and/or pituitary gland 40,41 …”
Section: Discussionsupporting
confidence: 76%
“…The increase in plasma prolactin levels observed after treatment with SOM3355 is consistent with that seen with other VMAT2 inhibitors, 39 and probably reflects a reduction in dopaminergic tone in the hypothalamus and/or pituitary gland. 40,41 Overall, the treatment in this trial with SOM3355 was safe and well-tolerated. The most frequent AEs were hypotension and bradycardia, which are consistent with the β 1 -adrenocepter blocking effect of bevantolol, but did not result in the discontinuation of the treatment; insomnia, which can be explained by the known effects of the drug, or because patients with HD are at increased risk of insomnia 37 (single fall rates between 21 and 75% and recurrent falls from 58 to 60% during early to mid-stage HD), with the consequent injuries and impact on their quality of life.…”
Section: Discussionmentioning
confidence: 79%
“…However, a recent study demonstrated that cells of the anterior pituitary gland can synthesise dopamine from L-DOPA by the local action of AADC. Moreover, locally produced dopamine was able to regulate PRL secretion [179]. We propose that our finding that Ddc is expressed in the adult pituitary gland and upregulated in pregnancy suggests an additional mechanism by which maternal PRL secretion is suppressed in gestation, and thus, merits further investigation.…”
Section: Imprinted Genes In the Pregnant Pituitary Glandmentioning
confidence: 71%
“…The mainly enriched pathway of Tyrosine metabolism involved in elevated levels of L-Dopa, HVA and Dopaquinone in AF patients with HF. In particular, HVA and Dopaquinone can be biosynthesized from L-Dopa, which was the precursor of dopamine [ 33 ]. As an endogenous catecholamine, dopamine worked as an autocrine and paracrine factor in the nonneuronal systems [ 34 ].…”
Section: Discussionmentioning
confidence: 99%